Kesadaran Konsumen dan Niat Membeli Jaminan Sosial Ketenagakerjaan Pada Pekerja Sektor Informal: Consumer Awareness and Intention To Buy Employment Social Security in Informal Sector Workers - Anwar, Ranti Fitri; Mulyati, Heti; Rahmawati, Wita Juwita (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Informal workers are considered as a marginal group often neglected in terms of protection in their work, especially employment social security. Indonesia is dominated by the number of informal workers inversely proportional to the number of participants in BPJS Ketenagakerjaan. This study intends to analyze the extent of influence and awareness level of informal workers about the BPJS Ketenagakerjaan program and to analyze the extent of informal workers intention to buy employment social security program. In this study, there are the independent variables; consumer awareness and intention to buy, while the dependent variable is employment social security participation. The analysis uses the Correlation Coefficient Test, the determination coefficient test, and the regression coefficient test. The results of this study indicate that the level of awareness of informal workers about employment social security is still categorized as low and the intention to buy the employment social security program for informal workers is also still categorized as low therefore BPJS Ketenagakerjaan needs to socialize in small quantities but massively and disseminate positive information related to BPJS Ketenagakerjaan and news about balance calculation, JHT fund management system. Keywords: BPJS Ketenagakerjaan, employment social security, consumer awareness, informal sector workers, intention to buy